Role-Playing, Witty Language, and Woman’s Agency in Oliver Goldsmith’s She Stoops to Conquer. (Raparin Journal of Humanities (RJH), 2025)
Oliver Goldsmith’s She Stoops to Conquer has been widely considered by critics as one of the most significant comedies in England’s 18th Century. Its popularity is due to the dramatist’s cunning use of satire and humour as artistic means of entertainment. Noticeably, critics mostly have focused on the aesthetic values of the dramatist’s use of satire and humour. However, this research provides a new reading, particularly the significance of the heroine’s bodily and linguistic role-playing. Firstly, the research investigates the extent the heroine’s role-playing enables the male protagonist to undergo personality change from a reserved and anti-social into a more tolerant and open-minded personality. Secondly, the research investigates the extent the heroine’s witty rhetoric, together with her role-playing, exposes patriarchal misconceptions, biases, and prejudices about women and marriage by the authoritarian figures. Notably, the easiness through which the heroine changes identities and social roles, symbolically, throws into question the fixability and naturalness of social roles in the play. Symbolically, the heroine’s performative acts of role-playing , whether bodily or linguistically, confirms postmodern feminist’s theory, particularly Third -Wave Feminism , with regard to  constructiveness and performativity of gender and identity. Methodologically, the research applies Close- reading approach; that is, New Criticism, as well as Feminist approach.  Moreover, the research is significant because it investigates the co-relation between the heroine’s role-playing and her quest for selfhood.